Drives and Control for Industrial Automation - Kiong T. K. Tan Kok (Advances in industrial control)
Drives and Control for Industrial Automation presents the material necessary for an understanding of servo control in automation. Beginning with a macroscopic view of its subject, treating drives and control as parts of a single system, the book then pursues a detailed discussion of the major components of servo control: sensors, controllers and actuators. Throughout, the mechatronic approach - a synergistic integration of the components - is maintained, in keeping with current practice. The authors holistic approach does not preclude the reader from learning in a step-by-step fashion - each chapter contains material that can be studied separately without compromising understanding. Drives are described in several chapters according to the way they are usually classified in industry, each comprised of its actuators and sensors. The controller is discussed alongside. Topics of recent and current interest - piezoelectricity, digital communications and future trends - are detailed in their own chapters. Presents the material necessary for an understanding of servo control in automation. This book offers a discussion of the major components of servo control: sensors, controllers and actuators. It is suitable for engineers and researchers interested in the applications of sensors, actuators and control systems in the automated environment.